2017
DOI: 10.1080/02770903.2016.1277541
|View full text |Cite
|
Sign up to set email alerts
|

Does the medical diagnosis of occupational asthma coincide with the legal diagnosis?

Abstract: This study verifies the importance of diagnosing asthma correctly as a first step in the evaluation of OA. Diagnostic tests other than specific provocation tests could be preferential in patients who still work in the same field. We believe that cooperation with the patient's occupational physician and adequate recognition of the work environment will improve the consistency of legal and medical diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The low education status and low-income level were thought to be the reason that patients could not reach health care services.Unlike our study, another study in our country found that 59.3% of participants did not receive influenza vaccination, 3% did not know the vaccine, and 22% did not believe in the preventive role of the vaccine. 11 In our study, knowledge about tetanus vaccination and tetanus immunization rate were significantly higher among the group with high education level (p D 0.04; p D 0.006). We did not find any significant difference between education status and pneumococcal and influenza vaccination knowledge and coverage.…”
Section: Discussionsupporting
confidence: 42%
“…The low education status and low-income level were thought to be the reason that patients could not reach health care services.Unlike our study, another study in our country found that 59.3% of participants did not receive influenza vaccination, 3% did not know the vaccine, and 22% did not believe in the preventive role of the vaccine. 11 In our study, knowledge about tetanus vaccination and tetanus immunization rate were significantly higher among the group with high education level (p D 0.04; p D 0.006). We did not find any significant difference between education status and pneumococcal and influenza vaccination knowledge and coverage.…”
Section: Discussionsupporting
confidence: 42%
“…Although it has been reported that even the use of a mask alone prevents the spread of respiratory viral pathogens because of its barrier (11), the effectiveness of enveloped viruses decreases with the use of soap, which is one of the hand hygiene practices (12). The widespread use of cologne as a disinfectant during the pandemic is another hygiene method that prevents the spread of viruses from person to person by providing fixation (13). In addition to the use of masks, other measures are also effective in reducing the incidence of non-COVID-19-URTI.…”
Section: Discussionmentioning
confidence: 99%